COVID-19 as a trigger for systemic diseases: a focus on systemic lupus erythematosus - I.V. Shop; T.M. Tykhonova; O.V. Al-Trawneh; N.I. Imanova; V.S. Oliinyk (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2025)
Background. COVID-19, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has profoundly impacted global health since its emergence. Beyond its acute respiratory symptoms, COVID-19 is recognized for its systemic effects, capable of impacting multiple organs and triggering a range of inflammatory and autoimmune responses. One area of growing concern is the potential of COVID-19 to induce or exacerbate systemic autoimmune-mediated diseases.